Síntese e caracterização de microcápsulas contendo óleo de tungue e aplicação em revestimentos alquídicos para proteção contra a corrosão - Cordeiro Neto, Alexandre Gonçalves (2019)
One of the biggest economic problems in the industry is the corrosion and the whole range of problems and secondary costs tied to this process. To avoid it commonly organic coatings are used to protect metal substrates. However, ordinary coatings are flawed and prone to weathering, losing their functionality quickly. An alternative to extend the life of the coatings is through the insertion of microcapsules in the coating matrix, transforming it into a smart coating. Smart coatings are coatings capable of responding to certain stimuli, acting independently without the need for human intervention, for repairs or maintenance. In this work microcapsules of ureaformaldehyde containing tung oil were synthesized by the in situ polymerization method. The microcapsules were characterized by the presence of Tungue oil by FTIR. Soon after the characterization they were incorporated into the matrix of a commercial monocomponent alkyd coating, and evaluations of the performance and the anticorrosive properties of this coating, which happened to be a smart coating, through the insertion of the microcapsules. These were added in the same proportion as the commercial corrosion inhibitor rich in zinc ions. These, together with a coating sample without anti-corrosive additives, were tested by means of corrosive saline 3.5% NaCl, simulating sea water. For this, the stimulus-responsive capacity of the microcapsules was demonstrated through mechanical disruption. It was observed that the additive coating presented an excellent performance for application in 1020 carbon steel specimens, maintaining properties such as gloss, adhesion and roughness improved or practically unchanged. The corrosion protection performance of the coating was evaluated by electrochemical analysis such as electrochemical impedance spectroscopy and open circuit potential and these tests showed that the microcapsules in the coating matrix caused a beneficial increase in the barrier property of the coating, besides protecting the metallic substrate when it undergoes a mechanical defect, through the release of the oil and its active protection conditioned to the coating.